Strategic Planning for Business Growth: A Qualitative Study on Product, Marketing, Operations, and Finance - Bona Panukunan Alexander Nainggolan (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to develop a business plan for the establishment of Roti Mom B&B in South Cikarang by evaluating business feasibility and formulating strategic approaches to support sustainable growth in the food and beverage industry. Design/Methodology/Approach – This study employs a descriptive qualitative research approach. Data were collected through observations and literature reviews. The business feasibility analysis focuses on five key aspects: product, marketing, operations, organization, and finance. These aspects were examined to identify business opportunities, challenges, and strategic development plans for the proposed physical store expansion. Findings – The results indicate that Roti Mom B&B has strong potential for market expansion due to consistent product quality and growing consumer demand. However, several challenges were identified, including limited human resources and insufficient digital marketing optimization. The proposed development strategies include strengthening operational systems, implementing targeted digital marketing strategies, and establishing a more structured organizational system. Based on the analysis, opening a physical store in South Cikarang is considered feasible and has the potential to increase revenue and strengthen market positioning. Originality/Value This research is original in integrating product, marketing, operations, organizational, and financial analyses into a comprehensive business plan for a start-up bakery café. The findings provide practical value by offering actionable strategies to optimize operational systems, digital marketing, and organizational structure for long-term business success.